Base‐Induced Cyclization of Propargyl Alkenylsulfones: A High‐Yielding Synthesis of 4, 5‐Disubstituted 2H‐Thiopyran 1, 1‐Dioxides. Issue 27 (14th August 2015) - Hatial, Ishita; Das, Joyee; Ghosh, Ananta K.; Basak, Amit
Abstract: A convenient synthesis of 4, 5‐disubstituted 2 H ‐thiopyran 1, 1‐dioxides is reported through a base induced process starting from eneyne sulfones. Except for strongly electron‐withdrawing groups, the reaction tolerated a wide variety of substituents in the two aryl rings. This finding represents a major departure from the behaviour of the corresponding ethers. The reaction most probably proceeds through a 6π‐electrocyclization from an in‐situ‐generated 1, 3, 5‐trienyl sulfinate. Abstract : The base‐induced cyclization of eneynesulfones to give 2 H ‐thiopyran 1, 1‐dioxides is described.